A new approach to the nutritional status of manganese in oil palm plants cultivated in the eastern Amazon - de Jesus Matos Viégas, Ismael; da Silva, Sávia Poliana; de Souza, Luma Castro; de Oliveira Ferreira, Eric Victor; Costa, Milton Garcia [UNESP]; da Silva Barata, Henrique (FapUNIFESP (SciELO), 2023)
Little is understood about the nutritional status of manganese (Mn) in oil palm (Elaeis guineensis Jacq.), further research is needed to provide technological support for greater productivity, especially on the dynamics of accumulation, recycling, immobilization and export. Thus, the objective of this work was to evaluate the dynamics of accumulation, immobilization, recycling, exportation and the efficiency of Mn use in oil palm plants at different ages. The experiment was carried out in a completely randomized design, with seven treatments (plant age: 2, 3, 4, 5, 6, 7, and 8 years of planting) and four replicates. The leaflets and male inflorescence were, the vegetative and reproductive organs with the highest Mn concentration, respectively. The accumulation of this nutrient in the tree crown predominated in the stipe through all years. The bunch exported the highest amount of Mn, especially in older plants. The oil palm immobilizes and recycles, more than exports, a large amount of Mn. The Mn use efficiency is increased as a function of the age of the crops in all the oil palm organs. In conclusion, the nutritional demand of oil palm is altered as a function of age, altering the dynamics of immobilization, recycling and exportation of Mn.
Keywords: Elaeis guineensis Jacq.; Mn export; Mn immobilization; Mn recycling; Mn use efficiency